Psychological well-being and its relationship to psychological flow among university teachers - AL-thahabee, Hanaa (Al-Adab Journal, 2025)
The current research aims to identify the level of psychological well-being and psychological flow among university teachers, and to identify the significance of the statistical difference in psychological well-being and psychological flow among university teachers according to the variables of gender (male - female), and to identify the relationship between psychological well-being and psychological flow among university teachers, the researcher relied on adopting two measures, the first being the (psychological well-being) scale by (Ryff 1995). Translated into Arabic by (Taha 2008), which in its final form consists of (54) paragraphs, divided into six areas: - (the purpose of life, self-acceptance, independence, positive relationships with others, personal maturity, mastery of the environment) ,The second scale (Psychological Flow) by (Jackson & Marsh 1996), which based on the theory of (Csikszentmihalyi 1996) and translated into Arabic by (Al-Ukaili and Al-Mohammadawi 2015), which in its final form consists of (34) items distributed over nine areas, which are: - (Balance between challenge Skill, the integration of awareness into action, clear goals, unambiguous feedback, focus on the task, a sense of precision, lack of self-consciousness, a sense of the passage of time, and self-pleasure The scale was applied to the basic sample of (150) teachers from universities in Baghdad for the academic year (2023-2024), and the results were: - The sample of the current research has high level of psychological well-being and psychological flow. There are also differences between males and females and in favor of males in well-being. Psychological well-being and psychological flow, and there is a direct relationship between psychological well-being and psychological flow among university teachers.